A new experiment to test parity symmetry in cold chiral molecules using vibrational spectroscopy. (March 2019) - Cournol, A.; Manceau, M.; Pierens, M.; Lecordier, L.; Tran, D.B.A.; Santagata, R.; Argence, B.; Goncharov, A.; Lopez, O.; Abgrall, M.; Le Coq, Y.; Le Targat, R.; et al.
Abstract: We present a brief review of our progress towards measuring parity violation in heavy-metal chiral complexes using mid-IR Ramsey interferometry. We discuss our progress addressing the main challenges, including the development of buffer-gas sources of slow, cold polyatomic molecules, and the frequency-stabilisation of quantum cascade lasers calibrated using primary frequency standards. We report investigations on achiral test species of which promising chiral derivatives have been synthesised.